Ionogels Obtained by Thiol-Ene Photopolymerization—Physicochemical Characterization and Application in Electrochemical Capacitors - Agnieszka Marcinkowska; Piotr Gajewski; Katarzyna Szcześniak; Mariola Sadej; Aneta Lewandowska (Molecules, 2021)
Flexible ionogels with good mechanical properties were obtained in situ by thiol-ene photopolymerization of trimethylolpropane tris(3-mercaptopropionate) (TMPTP) and 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (TATT) (with C=C: SH ratio 1:1) in four imidazolium ionic liquids (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide—EMImNTf2, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate-EMImOTf, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide-BMImNTf2, and 1-butyl-3-methylimidazolium trifluoromethanesulfonate—BMImOTf) used in the range 50 to 70 wt.%. The mechanical and electrochemical properties of obtained ionogels were examined. Ionogels with ionic liquids (ILs) with NTf2− anion are more puncture resistant than with OTf− anion. Moreover, ionogels with the NTF2− anion have better electrochemical properties than those with the OTf− anion. Although it should be noted that ionogels with the EMIm+ cation have a higher conductivity than the BMIm+. This is connected with intermolecular interactions between polymer matrix and IL related to the polarity of IL described by the Kamlet-Taft parameters. These parameters influence the morphology of the polymer matrix (as shown by the SEM micrograph), which is formed by interconnected polymer spheres.